1993
DOI: 10.1007/bf00191489
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and geotectonic setting of Late Proterozoic Katangan basic rocks from Kibambale in central Shaba (Zaire)

Abstract: The Late Proterozoic Katangan basic rocks (dolerites and basalts) outcropping at Kibambale in central Shaba (Zaire) are classified as extension-related tholeiites. The concentrations of immobile major and trace elements resemble those encountered in Phanerozoic enriched oceanic ridge basalts (E-MORB) emplaced in incipient oceanic rifts such as Red Sea and Tadjura Gulf troughs. This conclusion is also sustained by: elemental ratios which are MORB-like; multielement chondrite-and MORB-normalized patterns; sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The Grand Conglomérat and Roan Group sedimentary units pre-date the Lufilian orogeny. Mafic igneous rocks from Roan and Grand Conglomérat have geochemical features of magmas emplaced in East-African-type and Rea-Sea-type rift systems, respectively (Manteka et al, 1985;Kampunzu et al, 1991Kampunzu et al, , 1993Kampunzu et al, , 2000Tembo et al, 1999). The sedimentary succession of the Roan Group includes a conglomerate-sandstone-siltstone-shale and carbonate association, taken for a rift sequence by several authors (Raybould, 1978;Buffard, 1988;Cailteux, 1994).…”
Section: Geological Frameworkmentioning
confidence: 97%
“…The Grand Conglomérat and Roan Group sedimentary units pre-date the Lufilian orogeny. Mafic igneous rocks from Roan and Grand Conglomérat have geochemical features of magmas emplaced in East-African-type and Rea-Sea-type rift systems, respectively (Manteka et al, 1985;Kampunzu et al, 1991Kampunzu et al, , 1993Kampunzu et al, , 2000Tembo et al, 1999). The sedimentary succession of the Roan Group includes a conglomerate-sandstone-siltstone-shale and carbonate association, taken for a rift sequence by several authors (Raybould, 1978;Buffard, 1988;Cailteux, 1994).…”
Section: Geological Frameworkmentioning
confidence: 97%
“…Regional correlations Shackleton (1973) and Hanson et al (1988) suggested that the Irumide belt and the Choma-Kalomo block were two segments of the same belt cross-cut by the Neoproterozoic Zambezi belt. Kampunzu et al (1991Kampunzu et al ( , 1993Kampunzu et al ( , 2000 showed that igneous rocks exposed in the adjacent Damaran-Katangan segments of the Pan African orogenic system represent continental rift and Red-Sea-type mafic rocks, supporting limited development of Neoproterozoic seafloor along this trend, and therefore allowing the possibility of a linkage between the Irumide belt and Choma-Kalomo block. However, based on the presence of yoderite-bearing whiteschists in the Zambezi belt, Johnson and Oliver (2000) argue for the closure of a major Neoproterozoic ocean during convergence between the Congo and Kalahari cratons.…”
Section: Metamorphic Indicatorsmentioning
confidence: 98%
“…The Roan Group is made up of siliciclastic and carbonate sedimentary rocks (fluviatile and lacustrine sediments; Buffard, 1988;Cailteux et al, 1994), and volcanic and plutonic mafic rocks emplaced in a continental rift (Kampunzu et al, 2000 and references therein). The Nguba supracrustal assemblage is made up of siliciclastic and carbonate sedimentary rocks (François, 1974;Buffard, 1988) and includes mafic igneous rocks emplaced in a proto-oceanic rift similar to the Red Sea (Kampunzu et al, 1991(Kampunzu et al, , 1993Manteka et al, 1985;Kapenda et al, 1998). Kundelungu sedimentary rocks represent syn-to post-orogenic sedimentary deposits (Kampunzu and Cailteux, 1999).…”
Section: Geological Settingmentioning
confidence: 98%